2017
DOI: 10.1080/17482631.2017.1379339
|View full text |Cite|
|
Sign up to set email alerts
|

Transforming identity through participation in music and theatre: exploring narratives of people with mental health problems

Abstract: Background: There is a growing understanding that mental health problems and prolonged contact with mental healthcare systems can affect people’s identities. Working with identity is an important element in mental health recovery. Purpose: In this article, we explore the significance of participation in a music and theatre workshop in terms of people`s experiences of identity. Design and methods: This is a qualitative study based on a hermeneutical phenomenological epistemology. Data were collected from in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
(48 reference statements)
0
16
0
1
Order By: Relevance
“…Again, the analysis revealed information about participants’ experiences of arts participation in various and diverse ways. These experiences refer to both longer identity narratives [10] and shorter, more expressive descriptions showing the complexity and variety of what arts participation bring to their lives. To formulate overarching themes requires an intensive analytical process [33].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, the analysis revealed information about participants’ experiences of arts participation in various and diverse ways. These experiences refer to both longer identity narratives [10] and shorter, more expressive descriptions showing the complexity and variety of what arts participation bring to their lives. To formulate overarching themes requires an intensive analytical process [33].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we have analyzed data from a qualitative research project focusing on recovery processes among people with long-term mental illness [31]. In two previous published articles from the same study, we have focused on what enables meaningful arts participation in a mental hospital setting [31] and explored how arts participation may transform identities among people with mental illness [10]. The first article showed that continuity and flexibility in arts activities, guided by arts professionals with a non-judgment attitude, enabled participation [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flere studier viser at kordeltakelse gir økt energi, økt selvtillit og tro på seg selv, samt at det har positiv effekt på helsen for øvrig (Dingle, Brander, Ballantyne & Baker, 2013;Vaag, Saksvik, Theorell, Skillingstad & Bjerkeset, 2013;Ørjasaeter, Stickley, Hedlund & Ness, 2017). Korsang oppleves av mange som en gledesfylt aktivitet som har potensial til å berike livet til deltakerne (Judd & Pooley, 2014).…”
Section: Ottar Nessunclassified
“…Demonstrating the relationality of narratives of recovery, several studies show how everyday activities that put us in touch with others are particularly valuable to create meaning. When doing activities together, the persons involved try out possible plots in collaboration, seeking to create narratives that make meaning to everyone involved (Lindström et al, 2013;Ørjasaeter et al, 2017;Reed et al, 2018;Ulfseth et al, 2015Ulfseth et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%